(untitled) (Contemporary Journal of Social Science Review, 2025)
As we know that the women despite contributing up half of the global population, women still face multiple barriers to success, such as the glass ceiling and sustainable career growth. It relates to the invisible barriers to career success that women face at work. The purpose of this empirical study is to focus on relationship between to analyze the impact of DEI on Glass Ceiling and sustainable carrier progression; a case of female athletes in Pakistan. The data was collected using self-administered questionnaires from the respondents belonging to the female athletes of Lahore. A sample of 236 female athletes was selected for data collection and survey was based on close ended questions. Data was analyzed using SPSS through correlation and regression analysis. The result indicates that there is positive relationship between DIE on Glass Ceiling and Sustainable Carrier Progression. The main limitation of this study was lack of time, lack of resources, small sample size and only focus on one city’s respondents.